Calcaneal distraction vs. cast immobilization for the preoperative treatment of patients with Danis–Weber type C ankle fractures: a case–control study - Song, Bing; Shi, Jisheng; Xu, Xiaohui; Hou, Xiangfeng; Jia, Jingkun; Pang, Tongtao (Frontiers in Surgery, 2024)
Introduction Ankle fractures require temporary fixation to allow swelling to subside prior to surgery; this is typically achieved using calcaneal distraction or cast immobilization. We compared the results of these methods in the treatment of Danis–Weber type C ankle fractures. Methods This retrospective study analyzed the data of 86 patients with Danis–Weber type C ankle fractures, of whom 40 underwent calcaneal distraction and 46 underwent cast immobilization. Clinical measures including preoperative detumescence time, daily swelling value, skin condition, and pain, SF-36 Health Survey (SF-36) score and ankle scores were compared between the two groups. Results Baseline characteristics did not differ significantly between the groups. Calcaneal distraction resulted in a lower preoperative detumescence time (6.22 ± 0.64 vs. 8.94 ± 0.82 days) and lower daily swelling values compared with cast immobilization, leading to a lower skin necrosis rate. Resting pain scores were significantly lower in the calcaneal distraction group than in the cast immobilization group at various postoperative time points (P < 0.05). Ankle function scores were higher in the calcaneal distraction group than in the cast immobilization group at 12 months postoperatively (P < 0.05), indicating improved outcomes. Additionally, the SF-36 quality of life scores of patients undergoing calcaneal distraction were notably superior to those in the cast immobilization group. Discussion Calcaneal distraction is superior to cast immobilization in reducing soft tissue swelling, alleviating pain, and enhancing ankle function recovery in patients with Danis–Weber type C ankle fractures. Early calcaneal distraction upon hospital admission is recommended to optimize surgical outcomes.